Enhancing Student Reading Interest through Library Management: A Case Study at SMK Muhammadiyah Imogiri - Ibnu Redha Al Farizi; Nailis Sa adah; Arifah Nurrahmawati; Silviana Siswanda (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – This study aims to investigate the implementation of library management at SMK Muhammadiyah Imogiri with the objectives of enhancing students' reading interest and identifying supportive and inhibitive factors influencing this process. Design/methods– The research utilizes a descriptive qualitative methodology. Data collection involved observations, structured interviews, and document analysis. The data analysis was conducted following the Miles and Huberman approach, enabling a comprehensive understanding of the library management's impact on students' reading interest. Findings – The study's findings highlight that strategic planning, organizational efficiency, leadership, and control within library management are crucial in fostering students' reading interests. It also brings to light the significant role of libraries in education and the challenges they face, including limited resources and the influence of technological distractions on reading motivation. Research implications/limitations – While providing valuable insights, this research is limited by its focus on a single institution, which may affect the generalizability of the findings. The study paves the way for future research to be conducted in more diverse educational settings and potentially incorporate quantitative methods for a more comprehensive evaluation. Practical implications – The research emphasizes the need for robust library infrastructure and proactive human resource management in educational institutions. It underscores the importance of well-managed library resources and technology in promoting a reading culture among students. Originality/value –This study contributes original insights into the role of library management in enhancing students' reading interest, especially in the context of a vocational high school in Indonesia. It underscores the evolving challenges faced by libraries in the digital age and suggests the exploration of digital libraries and online resources as a valuable direction for future research.